Is Uterocervical Angle Associated with Gestational Latency after Physical Exam Indicated Cerclage? - Swanson, Kate; Grobman, William A.; Miller, Emily S. (American Journal of Perinatology, 2018)
Objective Prediction of gestational latency after placement of physical exam indicated cerclage (PEIC) is limited. Uterocervical angle (UCA) has been associated with spontaneous preterm delivery in the general population. Our objective was to examine whether UCA is associated with gestational latency in women with PEIC.Study Design This retrospective cohort included women with a singleton gestation who had PEIC placed at a single tertiary care center between January 2010 and September 2015. Ultrasound images of the cervix obtained prior to placement of PEIC were reviewed. Spearman's correlation coefficient for the relationship between UCA and gestational latency was estimated. UCA was dichotomized at 95° and 105°. Survival analyses were performed and Cox proportional hazard ratios were calculated.Results Sixty women met the inclusion criteria. Median gestational latency was 93 days (IQR 39–121 d). There was no significant correlation between UCA and gestational latency (Spearman's rho 0.08, p = 0.54). Survival analyses demonstrated no significant difference in gestational latency stratified by UCA ≥ 95° (HR 1.19, 95% CI 0.70–2.04) or UCA ≥ 105° (HR 0.95, 95% CI 0.56–1.63). Findings persisted after adjusting for potential confounders (aHR 1.29, 95% CI 0.74–2.23 for UCA ≥ 95° and aHR 1.04, 95% CI 0.60–1.82).Conclusion UCA is not associated with gestational latency in women with PEIC.
Keywords: physical exam indicated cerclage; uterocervical angle; transvaginal ultrasound; gestational latency